High-resolution continuum source flame atomic absorption spectrometric (HR-CS FAAS) determination of trace aluminium and lead in water and some beverage samples after separation and preconcentration procedure - Ciftci, Harun; Er, Cigdem; Yalcinkaya, Ozcan; Temuz, M. Mursit; Turker, Ali Rehber (Taylor & Francis Ltd, 2014)
In the present study, a solid phase extraction procedure has been presented for the separation and preconcentration of aluminium (Al) and lead (Pb) in various matrixes such as water, cola and fruit juice samples. 4-[(3-amino-5-{[(2-hydroxyphenyl) methylidene] amino}-1H-pyrazol-4-yl) diazenyl] benzoic acid (AHPMAPDAB) was used as a ligand. AHPMAPDAB chelates of Al and Pb ions in aqueous solutions were adsorbed on polystyrene-graft-ethyl methacrylate copolymer (Poly S-15-g-EMA(120)). Various experimental and analytical parameters such as sample solution pH, sample volume, flow rate of sample solution and eluent, volume and concentration of eluent, amount of ligand and adsorbent, effect of common matrix ions and capacity of adsorbent were investigated. The adsorbed metal ions on resin were eluted with 6mL of 2molL(-1) HCl solutions and their concentrations were determined by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). Under the optimised conditions, limits of detections were 0.32 mu gL(-1) and 0.24 mu gL(-1) for Al and Pb, respectively. The accuracy of the procedure was confirmed by analysing certified materials (NIST SRM 1643e, Trace elements in water) and spiked real samples. The developed procedure was successfully applied to real samples.
Keywords: preconcentration; beverages; lead; aluminium; continuum source atomic absorption spectrometry; graft polymer